(untitled) (The International Journal for Scientific Research, 2026)
The study investigated the impact of heat stress (40°C) versus moderate conditions (22°C) on the kinematic efficiency and physiological response of 200m runners. Ten elite U20 athletes were tested using a repeated measures design. Results revealed a cumulative, kinematic deterioration, with mechanical speed loss peaking at 11.1% in the final 50m segment. Lactic acid concentration increased by 40.4%, and skin temperature by 14.7%. The study concluded that thermal stress reduces "tendon stiffness" and impairs the stretch-shortening cycle (SSC), leading to significant stride length reduction and inefficient neural compensation through increased frequency